Anti-inflammatory activity and metabolite profiling of myo-inositol in LPS-stimulated macrophages - Marwa Seif; Lina Dahabiyeh; Afnan Al‐Hunaiti; Mohammad Semreen; Malek Zihlif; Hamzeh Al-Ameer; Amer Imraish (PLoS ONE, 2026)
There has been increasing interest in using dietary bioactive substances to alleviate and reduce inflammation. This study aims to assess myo-inositol’s possible anti-inflammatory effects, especially in handling conditions associated with macrophage activity. In this context, myo-inositol coated with polyethylene glycol (PEG) was created as a drug delivery system, and the macrophage cell line RAW 264.7 was used to evaluate its cytotoxicity. Additionally, their ability to suppress pro-inflammatory gene expressions induced by lipopolysaccharide (LPS) was investigated by determining the expression of pro-inflammatory genes such as interleukin (IL)-6, IL-1β, and tumor necrosis factor (TNF)-α. Furthermore, the molecular mechanisms and metabolic pathways affected by myo-inositol treatment were evaluated using a mass spectrometry-based metabolomics approach. PEGylated myo-inositol exhibited slight toxicity against RAW 264.7 cells with IC 50 values 124.9 μg/ml. However, myo-inositol did not exhibit toxicity over RAW 264.7 cells. In LPS-stimulated RAW 264.7 cells, PEGylated myo-inositol at concentrations of 31.2 and 15.6 μg/ml significantly reduced the expression of pro-inflammatory cytokines IL-6, IL-1β, and TNF-α at both the mRNA and protein levels. Moreover, PEGylated myo-inositol at 31.2 μg/mL reduced nitric oxide (NO) production by approximately 11.5-fold compared to the LPS group, further supporting its anti-inflammatory and immunomodulatory potential. The Metabolomics study identified 156 metabolites and revealed that the PEGylated myo-inositol significantly altered the metabolic profile of RAW 264.7 compared to the LPS-stimulated RAW 264.7. Metabolomics showed that the treatment alters the level of metabolites involved in the essential process of pro-inflammatory macrophages including energy metabolisms (e.g., TCA cycle, fatty acid oxidation), amino acids metabolisms (e.g., arginine and tyrosine), pyrimidine and purine metabolism, and lipids metabolism (e.g., 8,11,14-eicosatrienoic acid, sphinganine). Hence, PEGylated myo-inositol reversed some of the LPS impacts. Our Findings indicate that PEGylated myo-inositol exerts a promising anti-inflammatory effect through variant pathways. This can assist in developing the use of PEGylated myo-inositol for inflammatory diseases.